Morphogenesis of membrane topologies - Chun, Wang Xuan (Nanyang Technological University, 2020)
Myelins are cylindrical, multilamellar protrusions, which form when a dry mass of surfactants, phospholipids or amphiphilic polymers are subjected to an infusion of water. Structurally, they exhibit alternating layers of bilayers and aqueous channels, stabilized by an equilibrium interlamellar repulsive interaction. With sustained hydration gradient as the driving force, the protrusions can extend to tens of micrometres in diameter and hundreds of micrometres in length. The majority of reports have focused on Myelins consisting of a single molecular species. My thesis focuses on the formation of myelin from a complex mixture lipid, namely POPC (1-palmitoyl-2-oleoyl-glycero-3-phosphocholine) which is normally used for biophysical experiments as a model lipid, cholesterol and sphingomyelin, and examination of different methods to load hydrophilic molecules into the alternating aqueous channels. The diameter, length and growth rate of the ternary component Myelins are similar to that of the one component myelin, reported by other studies. In the first loading method, direct hydration of the dry mass with aqueous solution containing small molecules (molecular size < 2 nm in diameter) gives rise to immediate loading of the interlamellar space with the molecules, consistent with the size exclusion property of myelin. In the second method, loading of hydrophilic molecules post-myelin formation was tested. This method is inspired by the observation that the ternary component myelin exhibits continuous gradients of compositions across the lamella, when the dry lipid mass was doped with two phase-sensitive fluorophores. The fluorescence profiles suggest that the outer lamellae are enriched in sphingomyelin and cholesterol, which is immediately susceptible to MβCD treatment. Methyl-beta-cyclodextrin (MβCD) treatment, which extracts cholesterol, resulted in dramatic membrane remodelling. Infusion of hydrophilic molecules during the membrane remodelling phase leads to loading of the aqueous, interlamellar space with the hydrophilic molecules. Mechanical agitation transformed the interconnected structures into isolated vesicular morphology. In contrast, no visible loading was detected absent of MβCD-induced remodelling process, indicating that the loading is triggered by MβCD treatment. In conclusion, the result suggests that dynamic membrane structures, such as myelin, may potentially be useful for loading of drug compounds into membranous delivery vehicles.